Reply to the Correspondence on "How Aromatic Are Molecular Nanorings? The Case of a Six‐Porphyrin Nanoring". (11th July 2022) - Casademont‐Reig, Irene; Soriano‐Agueda, Luis; Ramos‐Cordoba, Eloy; Torrent‐Sucarrat, Miquel; Matito, Eduard
Abstract: A recent article by Anderson and co‐workers challenges our conclusions on the aromaticity of the four oxidation states of a butadyine‐linked six‐porphyrin nanoring, based on the experimental 1 H‐NMR data and some recent calculations they have performed using the BLYP35 functional. Here, we show that BLYP35 should be taken with caution and demonstrate that the indirect evidence of a ring current from experimental 1 H‐NMR data is not a definite proof of aromaticity. Abstract : Ring‐current strengths are a useful aromaticity measure that is obtained indirectly through the ring‐current model using experimental 1 H‐NMR data. The computation of ring currents provides direct visual aid and reveals that the ring‐current model overestimates the ring‐current strength of large molecular rings. Ring‐current plots show that c‐P6[ b 6 ]⋅T6 6+ (left) is much less aromatic than benzene (right).